Estudo de vacâncias em grafeno via cálculos de primeiros princípios - Paz, Wendel Silva (2013)
In this work, we have investigated the electronic, magnetic and structural features of graphene sheets containing atomic vacancies by using rst principle calculations based on density functional theory (DFT). Two di erent types of defects were considered: (i) single vacancies and (ii) divacancies. To this end, we have created a single vacancy and a divacancy by removing one or two carbon atoms from the pure graphene sheet, respectively. From the structural point of view, our results showed that a local distortion occurs around the vacancies. In particular, in the case of a divacancy the formation of pentagon and octagon structures with reconstruction of all dangling bonds was observed, resulting in a non-magnetic ground state. On the other hand, in the case of a single vacancy the reconstruction of two dangling bonds was detected, with the third atom with a dangling bond remaining in the plane. In order to verify the existence of possible metastable solutions involving di erent geometries of the graphene sheet containing a single vacancy, we have investigated in detail the possible displacement of this third atom perpendicularly to the sheet. In this case, the ground state was found to be magnetic and planar, with both ?? and ?? bands contributing to the total magnetic moment of the system, but metastable non-magnetic solutions could be achieved if an initial out-ofplane displacement of the third atom above 0.5 Å is provided. Finally, we have examined the hyper ne properties of graphene sheets with di erent types of carbon vacancies. The results showed that signi cant values of the hyper ne magnetic eld are found at nuclei of atoms with dangling bonds and in their neighborhood. Additionally, we have observed that there exists a nearly linear correlation between magnetic moment (per carbon atom) and hyper ne magnetic eld for all defects studied herein.